Modelling of longitudinal forces in a rail track to assess the stability of a track without joints (Международный научный журнал «Инженер», 2026)
The paper considers modelling of longitudinal forces in the rail track of a trackless track taking into account temperature and dynamic factors. The influence of rolling stock braking on track stability is analysed, including additional longitudinal loads caused by changes in rail temperature and the influence of traction currents. Mathematical models describing the formation of longitudinal forces, their influence on track deformations and conditions of safe operation are developed. Methods for measuring and controlling longitudinal forces are presented, as well as recommendations for monitoring and preventing critical loads that can lead to loss of stability.